2019
DOI: 10.1111/1365-2656.12944
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific patterns of senescence in Nazca boobies linked to mating system

Abstract: Under life‐history theories of ageing, increased senescence should follow relatively high reproductive effort. This expectation has rarely been tested against senescence varying between and within the two sexes, although such an approach may clarify the origins of sex‐specific ageing in the context of a given mating system. Nazca boobies (Sula granti; a seabird) practise serial monogamy and biparental care. A male‐biased population sex ratio results in earlier and more frequent breeding by females. Based on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(109 citation statements)
references
References 87 publications
(212 reference statements)
5
103
1
Order By: Relevance
“…To test for sex differences in ageing patterns, we adopted a similar approach to Tompkins and Anderson () and fitted six models for each trait (Table S1). In model 1, age was included as a quadratic function, and males and females were assumed to follow the same age trajectory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test for sex differences in ageing patterns, we adopted a similar approach to Tompkins and Anderson () and fitted six models for each trait (Table S1). In model 1, age was included as a quadratic function, and males and females were assumed to follow the same age trajectory.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, not all studies that have looked for sex differences in polygynous species have found them (Tidière et al, 2014(Tidière et al, , 2015Toïgo & Gaillard, 2003), and more generally, the evidence for a direct role of sexual selection on rates of ageing is equivocal (Bonduriansky, Maklakov, Zajitschek, & Brooks, 2008;Graves, 2007;Maklakov, Bonduriansky, & Brooks, 2009). This is likely because males and females can compete in different ways, the traits involved can entail different costs, and might also be expressed at different stages of lifespan (Clutton-Brock, 1983;Ralls & Mesnick, 2009;Stockley & Bro-Jørgensen, 2011;Tompkins & Anderson, 2019). In this context, it is important to appreciate that sex differences in survival rates and senescence depend on the characteristics of the two sexes which, in turn, depend on the specific selection pressures generated by intraspecific competition in the two sexes rather than on sex differences in reproductive variance (Clutton-Brock, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Recent correlative evidence suggests that population structure, such as sex-ratio, affects individual reproductive effort with potential sex-specific consequences on senescence [34,35]. In particular, variation in sex-ratio is predicted to modulate the cost of mating, through the strength of sexual selection in males [36], influencing the putative trade-off between reproductive effort and somatic maintenance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in polygynous species, strong sexual selection and intrasexual competition are thought to accelerate senescence and may lead to high mortality rates in males (Clutton-Brock & Isvaran, 2007;Bonduriansky et al, 2008;Maklakov & Lummaa, 2013;Greiner et al, 2014;Beirne et al, 2015;Tidière et al, 2015; but see Lemaître et al, 2020). Conversely, in monogamous species where sexual selection is not as intense, senescence acts similarly on both males and females (Clutton-Brock & Isvaran, 2007) or shows only moderate biases towards either sex (e.g., Lecomte et al, 2010;Froy et al, 2017;Tompkins & Anderson, 2019). If sexual selection leads to high senescence one should expect to detect senescence among females in sex-rolereversed species -yet, senescence of females in sex-role-reversed species has remained understudied.…”
Section: Impact Summary (297 Words)mentioning
confidence: 99%